2016
DOI: 10.1063/1.4963365
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanoclusters in silica: Photoluminescent properties and their application for enhancing the emission of silicon nanocrystals in an integrated configuration

Abstract: We studied photoluminescence of ion implanted platinum nanoclusters embedded in silica. Pt ions were implanted at 2 MeV and the Pt nanoclusters were then nucleated by thermal treatment under either argon, air, or a reducing atmosphere of hydrogen and nitrogen. The nanoclusters showed broad photoluminescence spectra (400 to 600 nm) with a maximum intensity at 530 nm. The photoluminescence intensity of the Pt nanoclusters was sensitive to the ion fluence used during the ion implantation, and luminescence quenchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…As it is evident from this figure, the Pt-NCs in silica can emit light when excited at 355 nm, but not under excitation at 1064 nm. This PL emission from Pt NCs embedded in silica and sapphire has been observed before in previous works for low and high power laser excitation at 355 nm [21,37]. The PL spectra of both Pt-NCs and Au-NCs have a broadband emission from 400 to 700 nm range, but the PL peaks are 532 nm and 547 nm respectively, i.e.…”
Section: Resultssupporting
confidence: 84%
“…As it is evident from this figure, the Pt-NCs in silica can emit light when excited at 355 nm, but not under excitation at 1064 nm. This PL emission from Pt NCs embedded in silica and sapphire has been observed before in previous works for low and high power laser excitation at 355 nm [21,37]. The PL spectra of both Pt-NCs and Au-NCs have a broadband emission from 400 to 700 nm range, but the PL peaks are 532 nm and 547 nm respectively, i.e.…”
Section: Resultssupporting
confidence: 84%
“…Here we can notice that for Pt particles in silica or sapphire the spectrum is the same, except for the difference in intensity, with a peak centered at 530 nm and FWHM of about 140 nm. The PL emission from Pt particles in silica or sapphire comes from ultrasmall particles with size less than two nanometers 27,41 Then, the resemblances in experimental spectral PL emission for Pt particles in silica or sapphire suggest a similar size distribution for ultrasmall Pt particles in both matrices; regardless of the presence of larger plasmonic NPs as predicted by Mie fit analysis.
Figure 3PL spectra of Pt, Au and Ag NCs embedded in silica ( a ) and sapphire ( b – d ) matrices. Laser excitation corresponds to 355 nm wavelength and a low pump fluence of 0.5 mJ/cm 2 .
…”
Section: Results and Analisismentioning
confidence: 99%
“…Pt NPs were also synthesized in high-purity silica plates by means of a 2 MeV ion beam with a fluence of ~2.5 × 10 16 cm −2 , followed by an annealing at 600 °C for 60 minutes under RA. This thermal treatment promotes the sample damage recovery to obtain a defect free ion-implanted silica matrix 27,41 . The implanted ion fluences and the concentration depth profiles were determined by Rutherford Backscattering Spectrometry (RBS), with a 2 MeV 4 He ++ beam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Pt NCs has been mainly promoted with regard to their application in catalysis [15,16], and recently it has been reported that they are suitable for highly fluorescent emission systems synthesized by chemical methods [11,[17][18][19][20]. On the other hand, the synthesis and luminescent emission of embedded Pt NCs in a solid matrix have scarcely been studied [21][22][23]. Platinum NPs embedded in silica matrix by ion implantation have been previously synthesized and particular indications about the influence of annealing conditions on their growth and structure have also been reported [21].…”
Section: Introductionmentioning
confidence: 99%